2014
DOI: 10.1001/jamaophthalmol.2013.7987
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography Staging and Autofluorescence Imaging in Achromatopsia

Abstract: IMPORTANCE Evidence is mounting that achromatopsia is a progressive retinal degeneration, and treatments for this condition are on the horizon.OBJECTIVES To categorize achromatopsia into clinically identifiable stages using spectral-domain optical coherence tomography and to describe fundus autofluorescence imaging in this condition. DESIGN, SETTING, AND PARTICIPANTSA prospective observational study was performed between 2010 and 2012 at the Edward S. Harkness Eye Institute, New York-Presbyterian Hospital. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 34 publications
2
61
0
6
Order By: Relevance
“…Michaelides et al 23 reported that the FAF appearance was normal in five affected members of a GNAT2 family. In a recent study of 10 achromats, Fahim et al 24 suggested an age-dependent change in FAF, with younger patients exhibiting increased foveal autofluorescence (AF), whereas older patients had reduced AF with discrete borders corresponding to outer retinal defects on SD-OCT. Greenberg et al 25 also observed FAF abnormalities, including increased and/or decreased AF (n ¼ 17). However, again these were cross-sectional studies of relatively small size, with no longitudinal FAF data in ACHM published to date.…”
mentioning
confidence: 87%
“…Michaelides et al 23 reported that the FAF appearance was normal in five affected members of a GNAT2 family. In a recent study of 10 achromats, Fahim et al 24 suggested an age-dependent change in FAF, with younger patients exhibiting increased foveal autofluorescence (AF), whereas older patients had reduced AF with discrete borders corresponding to outer retinal defects on SD-OCT. Greenberg et al 25 also observed FAF abnormalities, including increased and/or decreased AF (n ¼ 17). However, again these were cross-sectional studies of relatively small size, with no longitudinal FAF data in ACHM published to date.…”
mentioning
confidence: 87%
“…Several clinical studies in recent years have investigated outer retinal architecture and foveal morphology in detail using high-resolution optical coherence tomography (OCT) and adaptive optics [12,13,14,27,29,30,31,32,33,34]. The macular appearance in OCT can show either normal lamination or variable degrees of disruption of the photoreceptor layers and loss of retinal pigment epithelium.…”
Section: Clinical Manifestation and Diagnosticsmentioning
confidence: 99%
“…In recent years, several studies have investigated photoreceptor morphology in ACHM [29,30,31,32,33,34]. Carroll et al [32] observed a severely disrupted cone mosaic in the fovea and parafoveal area of a single patient with mutations in CNGB3.…”
Section: Some Inconsistencies Regarding the Progressive Nature Of Mormentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty per cent (20.9%) of the eyes in their series had a hyper-type or mixed-type FAF, and this finding was significantly associated with loss of the ellipsoid zone line of the photoreceptors on OCT, suggesting that a larger hyper-FAF-type or mixed-FAF-type lesion may indicate a more severely damaged ellipsoid zone line 22. On the other hand, Greenberg et al 25 evaluated the autofluorescence features of achromatopsia and concluded that the area of HAF found in 71% of their patients likely reflected increased cone outer segment turnover, marked by intensified bisretinoid deposition in the RPE.…”
Section: Discussionmentioning
confidence: 87%